(untitled) (Ágora Journal, 2026)
This work aims to discuss the formation of Palestinian literature throughout the 20th and 21st centuries, considering its reverberations amidst colonial processes, British and Zionist, and the creation of the State of Israel in 1948. We consider literature as an integral part of the political and economic transformations in the Middle East region, and in Palestine specifically, reflecting on its social realities, especially those linked to imperialism and domination, and in this sense, on the possibility of elaborating (national) identity and resistance. Within this context, we will present an overview of the formation of this field, taking into account the different moments experienced by Palestinians, from the British presence to the establishment of Israel and, more recently, the last decades of occupation. We will analyze how the concern with territory has been present since the beginning of this colonial process, tracing literary and intellectual sensibilities, and presenting, historically, a guiding thread of this theme: the threat, the loss of land, and the possibilities of connection with the territory under contemporary occupation.